First Nations People and Energy Transition: How to Increase Employment in Clean Energy - Chris Briggs; Michelle Tjondro; Rusty Langdon; Sarah Niklas; Ruby Heard; Michael Frangos; Elianor Gerrard (Cosmopolitan Civil Societies: An Interdisciplinary Journal, 2025)
Training and employment will be a key determinant of whether the socio-economic position of First Nations peoples is improved through the energy transition, but there are few studies on how to increase First Nations employment in renewable energy. Our study, which focusses on Renewable Energy Zones in Australia, has four key findings. Firstly, employment and training mandates and incentives in government renewable energy auctions can increase First Nations employment, but a ‘coordinated flexibility’ approach is required which accommodates regional variations, differences in occupational structure between technologies and integrates First Nations businesses. Secondly, training-led initiatives have a poor job-creation record, but programs for school students and the unemployed are required to build the labour supply to meet procurement targets. Thirdly, wherever possible, demand and supply-side instruments should be integrated within clean energy programs (e.g. housing retrofits). Fourthly, complementary measures are required which resource industry to achieve targets, improve cultural safety in workplaces and build the capacity of First Nations organisations.